Persepsi Siswa terhadap Strategi Sekolah selama Masa Pandemi Covid-19 di SMA Negeri 1 Wonosari Kabupaten Klaten - Jordan, Edgar; Dewi, Ratih Puspita (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2022)
Abstract: The covid-19 pandemic turned conventional learning into online learning. Schools as educational institutions need to implement learning strategies during the covid-19 pandemic. This study aims to determine students' perceptions of school strategies during the covid-19 pandemic. The data collection techniques contained in this study are questionnaires, observations, and documentation. The data that has been obtained is then done analysis using descriptive statistical analysis. The results showed that on the indicator of online learning planning obtained the highest percentage of 42% of students agreed with the school's strategy of providing information about the covid-19 pandemic to teachers, students, and parents. On the indicator of the implementation of online learning, the highest percentage of 43% of students agreed with the school's strategy of providing information related to maintaining a healthy lifestyle during the covid-19 pandemic. In the online learning evaluation indicator, the highest percentage of 35% of students agreed with the school's strategy of identifying obstacles or problems found during learning. Given the importance of online learning strategies, it is expected that schools can develop strategies to support learning during the covid-19 pandemic. Keywords: Covid-19, Geography, Learning Strategy, School